The History of Moslem Intellectuals: A Case Study at UIn Syarif Hidayatullah Jakarta - Siregar, Parlindungan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This study aimed to explain that the intellectual community who studied at and was born from the state Institute of Islamic Studies Syarif Hidayatullah (IAIN Jakarta) in the 1970s to 1985 were the second-generation intellectuals who had their own characteristics. As the study was library research, the data collection was done by examining deeply the written documents or literatures that were relevant with the problems being investigated. The obtained data were then qualitatively analyzed by comparing and connecting the existing variables; and inferences were drawn from the findings to get an ideal concept of building a good national and state life based on the Islamic substantial values. The results of the study showed that second generation intellectuals became international intellectuals as Islamic historians in Southeast Asia, theologians, political or socio-economic analysts, and activists of Islamic movements. The study also pointed out that it was not only the first generation that made the second generation successful in their career and studies, but many factors on and off campus contributed significantly, and affect the next generations continuously from time to time. Evidently, in their development, discussion activities of intra-or extra campus organizations, talked not only about Islam but also political issues, such as the old order government policies. The study concluded that the second generation of IAIN Jakarta Intellectual community played many roles in Islamic studies in national and international level. It suggested that studies on the same topis with different points of views are still necessary to conduct.